Fungal Endocarditis After Hybrid Periventricular Closure of Muscular Ventricular Septal Defect by Amplatzer Occluder in a Child. Issue 6 (10th February 2015) - Bressieux-Degueldre, Sabrina; Sekarski, Nicole; Di Bernardo, Stefano
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.